النظام القانوني للموظف المتربص في التشريع الجزائري - سعيد, ايمن صابر; شنة, عبد الوهاب (My University, 2023)
تناولنا في هذه المذكرة النظام القانوني للمتربص في التشريع الجزائري ، وتمثل هذه المرحلة فيما يصطلح عليه المشرع الجزائري بفترة التربص باعتبارها كقاعدة عامة مرحلة ضرورية بالنسبة لكل شخص معين حديث التوظيف، إذ يجب عليه قضاء فترة تربص إجبارية لمدة زمنية محددة تسري ابتداء من تاريخ تعيينه في الرتبة والوظيفة المطلوب شغلهما ، فيأخذ المركز القانوني للشخص في هذه الفترة صفة المتربص . هذا ما تناولناه في الفصل الأول، في حين تطرقنا في الفصل الثاني مسار المتربص في مجال الوظيفة العمومية تجدر الإشارة إلى أن موضوع دارستنا لم يحظ باهتمام كبير في التشريع الجزائري للوظيفة العمومية إلا في الآونة الأخيرة وذلك ابتداء من تاريخ 2 نوفمبر سنة 2102 ، حيث أسفر عن هذا التاريخ صدور لأول مرة تنظيم قانوني خاص بالأحكام المطبقة على المتربص في المؤسسات والإدارات العمومية .Abstract In this note, we have dealt with the legal system for the intern in the Algerian legislation, and this stage represents what the Algerian legislator termed as the internship period, as a general rule, a necessary stage for each newly appointed person, as he must spend a compulsory internship period for a specific period of time starting from the date of his appointment to the rank And the job to be filled, so the legal status of the person during this period takes the status of a lurker. This is what we dealt with in the first chapter, while in the second chapter we touched on the path of lurking in the field of civil service It should be noted that the subject of our study did not receive much attention in the Algerian legislation for the public service until recently, starting from the date of November 2, 2102, as this date resulted in the issuance of for the first time a legal regulation of the provisions applicable to the lurking in public institutions and administrations.
مذكرة ماستر
Keywords: المتربص ، التربص ، الوظيفة العمومية ، المؤسسات والادارات العمومية ، النظام التأديبي .; lurking, lurking, public office, institutions and administrations General, disciplinary system